High-Risk Prescription Opioid Use Among People Living With HIV. (1st July 2018) - Canan, Chelsea E.; Chander, Geetanjali; Monroe, Anne K.; Gebo, Kelly A.; Moore, Richard D.; Agwu, Allison L.; Alexander, G. Caleb; Lau, Bryan
Abstract : Background: Prescription opioid use is greater among people living with HIV (PLWH), yet little is known about the prevalence of specific types of high-risk use among these individuals. Setting: We analyzed clinical and demographic data from the HIV Research Network and prescribing data from Medicaid for noncancer patients seeking HIV treatment at 4 urban clinics between 2006 and 2010. Methods: HIV Research Network patients were included in the analytic sample if they received at least one incident opioid prescription. We examined 4 measures of high-risk opioid use: (1) high daily dosage; (2) early refills; (3) overlapping prescriptions; and (4) multiple prescribers. Results: Of 4605 eligible PLWH, 1814 (39.4%) received at least one incident opioid prescription during follow-up. The sample was 61% men and 62% African American with a median age of 44.5 years. High-risk opioid use occurred among 30% of incident opioid users (high daily dosage: 7.9%; early refills: 15.9%; overlapping prescriptions: 16.4%; and multiple prescribers: 19.7%). About half of the cumulative incidence of high-risk use occurred within 1 year of receiving an opioid prescription. After adjusting for study site, high-risk opioid use was greater among patients with injection drug use as an HIV risk factor [adjusted hazard ratio (aHR) = 1.39, 95% confidence interval: 1.11 to 1.74], non-Hispanic whites [aHR = 1.61, (1.21 to 2.14)], patients age 35–45 [aHR = 1.94, (1.33 to 2.80)] and 45–55 [aHR = 1.84, (1.27 to 2.67)], and patients with a diagnosis of chronic pain [aHR = 1.32, (1.03 to 1.70)]. Conclusions: A large proportion of PLWH received opioid prescriptions, and among these opioid recipients, high-risk opioid use was common. High-risk use patterns often occurred within the first year, suggesting this is a critical time for intervention. Abstract : Supplemental Digital Content is Available in the Text.